Effect of clean agriculture on some qualitative indicators of coriander - Hala Mohammad; Mohamad ABD Elaziz; Roula Yacoub (Annals of Agricultural Research, 2022)
The lack of information on cultivation of coriander in Syria has reinforced the importance of the effect of two types of organic fertilizer (bovine compost and compost) at a rate of 15 tons/ha each, and four levels of EM1 (0.5, 1, 1.5)/L as paper feed and liters/dan as a radical feed on some of the specific qualities of coriander. The study was conducted at Syria (Tartous) during the agricultural season 2017 using the design complete random sectors according to the order of the splitting pieces twice for the studied transactions. The results showed that there were statistically significant differences between the coefficients for most studied traits. In addition, there was a mutual effect of organic fertilization and bio-fertilization concentrations. Although concentrations (0.5, 1, 1.5 ml/L) varied in effect, Compost bovine manure was superior in all studied traits. The concentration of 1.5 L/dunum was important in terms of increasing both the percentage of fixed oil, the percentage of the pilot oil and the content of the fruits of the nuts and protein. On the other hand, the method of root feeding played a role in increasing the proportion of oil, while paper feeding played a role in the content of the fruits of the nuts and protein.